Response Surface Modeling for the Enrichment of Gamma-Aminobutyric Acid with a Minimum Content of Citrinin in Monascus-Fermented Rice - Washim Khan; Omkar Regmi; Mojeer Hasan; Bibhu Prasad Panda (eFood, 2019)
γ-Aminobutyric Acid (GABA) is a secondary metabolite produced in Monascus-fermented food. The mycotoxin (citrinin), another major secondary metabolite, is neurotoxic to humans and thus it diminishes the social acceptability of Monascus-Fermented Rice (MFR). The study was aimed to enrich GABA content and to reduce citrinin level in MFR. Plackett–Burman experimental design and response surface methodology was used to optimize a fermentation medium for a high amount of GABA production with less amount of citrinin by Monascus purpureus Microbial Type Culture Collection and Gene Bank (MTCC) 369 under solid state fermentation (SSF). Statistically optimized nutrient parameters for MFR were lactose 0.054 g/g, alanine 2 mg/g, malt extract 37.4 mg/g, and ZnSO4 0.3 mg/g. The yield of GABA and citrinin in optimized conditions were found to be 24 ± 0.27 mg/g and 3.3 ± 0.19 μg/g, respectively. The optimized medium parameters can be used and explored to produce high amount of GABA with low citrinin in MFR.